2009
DOI: 10.1038/aps.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of endogenous mFlt4 displayed on a T4 phage nanoparticle surface

Abstract: Aim: Flt4 plays a key role in promoting tumor metastasis by stimulating solid tumor lymphangiogenesis. In this study, mouse Flt4 (mFlt4) was displayed on T4 phage in order to explore the feasibility of breaking immune tolerance to "selfantigens" and to evaluate the phage's antitumor activity. Methods: A T4 phage nanometer particle expressing mFlt4 on the surface was constructed for evaluation as a recombinant vaccine. The presence of the mFlt4 gene in the T4-mFlt4 recombinant vaccine was verified by PCR and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…, where 'A' represent the largest dimension of the tumor and 'B' indicates the smallest dimension [21].…”
Section: Measurement Of Cell Proliferation and Viabilitymentioning
confidence: 99%
“…, where 'A' represent the largest dimension of the tumor and 'B' indicates the smallest dimension [21].…”
Section: Measurement Of Cell Proliferation and Viabilitymentioning
confidence: 99%
“…In addition, they suppressed tumor metastasis. 12 Marker Ki67 is a nuclear protein found in the G1-phase of cell cycle and its expression is strictly associated with cell proliferation. The Ki67 antigen is a useful non-histonic protein, used to identify prolific cells that, not having phase specificity.…”
mentioning
confidence: 99%
“…Ren et al[116] found that displaying the appropriate peptide on the T4 capsid could stimulate an immune response. They, previously had shown that the separate respective genetic modification of SOC and HOC with the polyprotein and proteinase of foot-and-mouth disease virus (FMDV) produced 100% immunogenicity compared to the wild type of T4[117].…”
Section: Bacteriophages As Nanocarriersmentioning
confidence: 99%